A profile of children in the Avian park and Zweletemba settlements in the Breede Valley local municipality of the Western Cape Province, South Africa - Koornhof, Hilletjie Elizabeth (Stellenbosch : Stellenbosch University, 2014)
Thesis (Mnutr)--Stellenbosch University, 2014.